Dengue: development of preventive vaccines A systematic review - Pereira Mendonça, Kariny; Laube, Gerardo (SCT Proceedings in Interdisciplinary Insights and Innovations, 2024)
Introduction: Dengue is a viral disease transmitted by a vector, which has 4 different serotypes. This infection by any viral strain can be asymptomatic or cause variable and unique clinical manifestations ranging from a mild febrile syndrome to severe dengue. Because there is no treatment that acts effectively and the vector control measures are not as successful as expected to prevent or impede the proliferation of the virus, the formulation of a vaccine becomes an effective measure to stop the development of the disease. Material and methods: The present systematic review has used search engines such as Pubmed and Google academic to search for articles of the clinical and randomized trial type, finding articles regarding dengue and vaccination. Results: (A total of 15 RCTs have been used for a fundamentalistic analysis of the predefined variables to understand dengue and vaccination.). Conclusion: Dengue is the most widespread disease transmitted by mosquito bites in the world. This high prevalence shows the importance of vaccines in controlling the disease. Furthermore, it is worth highlighting the attention necessary for a diagnostic test due to crossimmunization. Thus we conclude that the greater the knowledge about the vaccines made and those that are in the development phase, taking into consideration a good diagnosis is of utmost importance for the control of the disease and its consequences